Serum protein coating enhances the antisepsis efficacy of silver nanoparticles against multidrug-resistant Escherichia coli infections in mice - Du, Huamao; Wang, Xiaoling; Zhang, Hongying; Chen, Heming; Deng, Xiaoyu; He, Yujing; Tang, Huaze; Deng, Fuchang; Ren, Zhihong (Frontiers in Microbiology, 2023)
Antimicrobial resistance poses a significant threat to public health and social development worldwide. This study aimed to investigate the effectiveness of silver nanoparticles (AgNPs) in treating multidrug-resistant bacterial infections. Eco-friendly spherical AgNPs were synthesized using rutin at room temperature. The biocompatibility of both polyvinyl pyrrolidone (PVP) and mouse serum (MS)-stabilized AgNPs was evaluated at 20 μg/mL and showed a similar distribution in mice. However, only MS-AgNPs significantly protected mice from sepsis caused by the multidrug-resistant Escherichia coli (E. coli) CQ10 strain (p = 0.039). The data revealed that MS-AgNPs facilitated the elimination of Escherichia coli (E. coli) in the blood and the spleen, and the mice experienced only a mild inflammatory response, as interleukin-6, tumor necrosis factor-α, chemokine KC, and C-reactive protein levels were significantly lower than those in the control group. The results suggest that the plasma protein corona strengthens the antibacterial effect of AgNPs in vivo and may be a potential strategy for combating antimicrobial resistance.